Synthesis of discrete drives control systems - Cherkashenko, M. V. (НТУ "ХПІ", 2018)
The classical methods of creation of schemes using tables of transitions, states, Carnot's cards and other means which dimension depends on number of inputs and outputs of the scheme are not acceptable for systems big dimension (with big number of inputs, outputs and internal states). Control systems of hydropneumatic units are the determined systems of big dimension. Now at synthesis of systems of hydropneumatic units the standard position structure having the known advantages, but which is characterized by a large number of elements of the projected scheme is used. Partial minimization of standard position structure was offered inthe works Yuditsky S., Goedecke W., Belforte G., Reydzo J., etc. The method of full minimization of the standard position structure offered by the author allowed to receive the minimum structure of schemes due to receiving of minimum the operation graph and the offered mathematical model – the matrix conformity (MC) which dimension does not depend on quantity of entrances and exits of system.

Класичні методи побудови схем, які використовують таблиці переходів, станів, карти Карно і інші засоби, розмірність яких залежить від числа входів і виходів схеми, не прийнятні для систем великою розмірністю (з великою кількістю входів, виходів і внутрішніх станів). А системи управління гідропневмоагрегатів є детермінованими системами великої розмірності. В даний час при синтезі систем гідропневмоагрегатів використовується стандартна позиційна структура, яка володіє відомими перевагами, але яка характеризується великою кількістю елементів проектованої схеми.
Синтез дискретних систем управління приводами
Keywords: standard position structure; matrix conformity; operation graph; hydropneumatic units; synthesis of systems; стандартна позиційна структура; матриця відповідностей; граф операцій; гідропневматична одиниця